HUBUNGAN ANTARA WHR DENGAN KADAR HS-CRP SERUM PADA MAHASISWA OBES DAN TIDAK OBES DI FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Toreh, Ezra; Kawengian, Shirley E. S.; Bolang, Alexander S. L. (Universitas Sam Ratulangi, 2013)
Abstract: Central obesity is recognized as a major factor that associated with increased risk for some chronic diseases. Waist to hip ratio described the increase in visceral adipose tissue and subcutaneous fat on waist circumference and hip circumference.C-reactive protein is the detection of cardiovascular disease risk in conventional but not sensitive enough to detect cardiovascular risk so beused the new method is of high sensitivity C-reactive protein.The research have purpose to know the difference and relationship of waist to hip ratio and high sensitivity c-reactive protein level between obese and non-obese students at Medical Faculty of Sam Ratulangi University Manado. This research was an observational analytic cross-sectional approach. The results of statistical analysis using the Mann-Whitney U test revealed that there were significant differences (p = 0.000 <0.05) both WHR and hs-CRP level in both groups of students are. Conclusion: The results of statistical analysis using the Spearman test showed that there is a positive very weak relationship (r = 0309) and significant (p = 0017 <0.05) between the values ??of WHR with hs-CRP level in obese and non-obese students at Medical Faculty of Sam Ratulangi University Manado. Key Words: WHR, hs-CRP Abstrak: Obesitas sentral diakui sebagai factor utama yang dikaitkan dengan peningkatan resiko untuk beberapa penyakit kronis. Waist to hip ratio (WHR) menggambarkan peningkatan jaringan adiposa visceral dan lemak subkutan pada lingkar pinggang dan lingkar pinggul. C-reactive protein (CRP) merupakan deteksi risiko penyakit kardiovaskular tapi secara konvensional tidak cukup sensitif untuk mendeteksi risiko kardiovaskular sehingga digunakan metode baru yaitu high sensitivity C-reactive protein (hsCRP). Penelitian bertujuan untuk mengetahui perbedaan dan hubungan waist to hip ratio (WHR) dengan kadar high sensitivity c-reactive protein (hs-CRP) serum pada mahasiswa obes dan tidak-obes di Fakultas Kedokteran Universitas Sam Ratulangi Manado. Penelitian ini bersifat observasional analitik dengan menggunakan pendekatan cross-sectional. Hasil analisis statistic dengan menggunakan uji Mann-Whitney U menunjukan terdapat perbedaan yang bermakna (p=0.000<0.05) baik WHR maupun kadar hs-CRP serum pada kedua kelompok mahasiswa tersebut. Simpulan: Hasil analisis statistic dengan mengguna-kan uji Spearman menunjukan bahwa terdapat hubungan yang positif sangat lemah (r=0.309) dan bermakna (p=0.017<0.05) antara nilai WHR dengan kadar hs-CRP serum mahasiswa obes dan tidak-obes pada Fakultas Kedokteran Universitas Sam Ratulangi Manado. Kata Kunci: WHR, hs-CRP